2010
DOI: 10.1111/j.1600-0765.2010.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to Aggregatibacter actinomycetemcomitans leukotoxin

Abstract: Systemic antibodies against A. actionmycetemcomitans leukotoxin were common in this adult Swedish population. These antibodies might contribute to limit the systemic effects of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 38 publications
4
39
1
Order By: Relevance
“…The serum was a commercial product that was pooled from many human donors, and a large proportion of individuals with periodontitis express antibodies against whole A. actinomycetemcomitans as well as A. actinomycetemcomitans leukotoxin. 31 Although it is likely that these antibodies produced similar effects on bacterial killing by the two antibiotics used in this study, it would have been useful to characterize the levels of antibodies in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…The serum was a commercial product that was pooled from many human donors, and a large proportion of individuals with periodontitis express antibodies against whole A. actinomycetemcomitans as well as A. actinomycetemcomitans leukotoxin. 31 Although it is likely that these antibodies produced similar effects on bacterial killing by the two antibiotics used in this study, it would have been useful to characterize the levels of antibodies in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…79,80 It has also been shown that systemic antibodies against LtxA efficiently neutralize the activity of the toxin, which might interfere with the pathogenicity of A. actinomycetemcomitans, both locally and systemically. 81 As described in detail above, LtxA induces a massive secretion of bioactive IL-1b from macrophages. Interestingly, a receptor protein for this cytokine with regulatory properties has been identified on A. actinomyctemcomitans, which indicates further interactions with the host inflammatory response.…”
Section: A Actinomycetemcomitans In the Complex Biofilm Of The Periomentioning
confidence: 92%
“…Whether the expressed and exported LtxA remains associated with the bacterial outer membrane or is secreted into the environment is a topic of controversy, and the mechanisms that keep the toxin associated with the membrane are still not fully understood. However, the serum-mediated release of the toxin (144, 145), as well as its highly systemic immunogenic response (146), indicate a substantial release of the toxin from bacteria growing in an oral biofilm in vivo .…”
Section: Leukotoxinmentioning
confidence: 99%
“…More recently, T-regulatory (Treg) and Th17 cells have been detected in periodontal tissues indicating that these cells are also important in the host response and pathogenesis of periodontal disease (168). The strong acquired systemic humoral immune response induced by LtxA indicates direct contact between this molecule and cells of lymphoid origin (146, 169). The ability of LtxA to induce apoptosis in lymphocytes might contribute to a locally impaired acquired immune response in periodontal infections.…”
Section: Leukotoxinmentioning
confidence: 99%
See 1 more Smart Citation